"Passengers, May I Have Your Attention Please..." - The Airport Diaries of Young COVID-19 Warriors - Shweta Gajare; Alhad Mulkalwar (University Library System, University of Pittsburgh, 2023)
This article summarizes the novel experiences of a team of medical interns posted at Chhatrapati Shivaji Maharaj International Airport, Mumbai in the midst of the COVID-19 Pandemic. The authors describe the protocols, guidelines, duties and procedures that were to be followed while deputed to screen the incoming international passengers for possible exposure and symptoms of coronavirus. For the young healthcare workers, in the early days of their internship, being a part of this team was no less than a roller coaster ride. From anxiety and excitement to fatigue and crippling exhaustion, the authors narrate their ordeal as young COVID warriors on duty.